1992
DOI: 10.1038/eye.1992.46
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of retinopathy of prematurity: A prospective study

Abstract: The natural history of retinopathy of prematurity (ROP) has been studied prospectively in 572 infants < or = 1,700 g birthweight using a protocol designed specifically to investigate the subtle features of this condition. Acute ROP developed in 50.9%. All ROP stages 1 and 2 underwent complete resolution and of the 27 (4.7%) infants with stage 3/4 disease, cicatricial sequelae developed in six. Incidence and severity increased with decreasing birthweight and gestational age. Onset was not confined to the tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0
9

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(83 citation statements)
references
References 34 publications
10
64
0
9
Order By: Relevance
“…While comparison between different racial groups was not possible in our study due to the small number of light coloured fundi, this study supports the findings of other studies [16][17][18] regarding the low occurrence rate of ROP especially of advanced disease in black patients or darkly pigmented fundi.…”
Section: Eyesupporting
confidence: 90%
“…While comparison between different racial groups was not possible in our study due to the small number of light coloured fundi, this study supports the findings of other studies [16][17][18] regarding the low occurrence rate of ROP especially of advanced disease in black patients or darkly pigmented fundi.…”
Section: Eyesupporting
confidence: 90%
“…6,7 Stage 3 ROP is unusual in babies born at or after 30 weeks gestation. Our unit has screened 2960 infants of whom stage 3 ROP has been found in five other babies with birth weight >1500 g. Their birth weights and GA were as follows: 1502 g, GA 32 weeks; 1560 g, GA 31 weeks; 1600 g, GA 31 weeks; 1600 g, GA 30 weeks; 1800 g, GA 31 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The receiver operator response curve depicts that the model could discriminate the risk factors in 85.66% of the babies weighing between 1501 and 1800 g correctly in babies weighing ≤1800 g was less as compared to various Western studies [7][8][9][10] and previous studies done in Indian scenario. [10,15] This study found low birth weight and low gestational age to be statistically signifi cant for the causation of ROP; as also has been found by authors of previous studies.…”
Section: Figure 1bmentioning
confidence: 99%
“…Incidence of ROP varies in different neonatal units. [5,7] It has been reported to vary from 21% to 65.8% [7][8][9][10] in western studies and 34.9-60.1%. [10,11] in Indian studies.…”
Section: Introductionmentioning
confidence: 99%